Development of a Holistic Nursing Model Based on Transcultural Nursing to Improve the Quality of Life of Patients with Type-2 Diabetes Mellitus - Ni Wayan Suniyadewi; Yuni Sufyanti Arief; Ninuk Dian Kurniawati; I Dewa Ayu Rismayanti; Ni Wayan Trisnadewi; Iswatun Iswatun (Nurse Media: Journal of Nursing, 2024)
Background: The management of type 2 diabetes mellitus (T2DM) primarily emphasizes physical care, yet the quality of life (QoL) remains suboptimal. The management of diabetes often neglects psychological, socio-cultural, and spiritual aspects, which are essential components of transcultural nursing. Developing a holistic nursing model rooted in transcultural nursing, which has never been broadly investigated, is imperative to enhance QoL in individuals with T2DM.